POLITIK PEMBANGUNAN INDONESIA CENTRIS SATU PERUBAHAN MENDASAR BAGI PENINGKATAN KESEJAHTERAAN RAKYAT - Mr. Suwandi (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2016)
This research has objective to described political development in indonesia and the process of theÂ funding for. Renewing and innovation is part of identity the nation to escape from dependence and interfering the hands of the people alien to independence .Human development completely, good born and inner, performed with balanced , so that the state of having strength in face the challenges , obstacles, and disorders coming from outside. By a mood of safe, the government can do development by baik.namun, still there is a shortage of and the advantage, during which time, development is centered in java, so that the economic growth also centralized in Java Island. A prosperity and welfare will be fulfilled when every citizen indonesia participated in development, so that changes the pattern and lifestyle that so far disadvantaged and can see positive change from the development. Innovation and updating very required to change road map develop indonesia sustainable to stay mengedepankan and respect local genius.